ORGANIZING PROJECT-BASED ACTIVITIES BASED ON STEAM TECHNOLOGY IN PRESCHOOL EDUCATION INSTITUTIONS - Dilnoza Gafurova Saloxiddinovna (Web of Journals Publishing, 2025)
This article highlights the importance of the project-based method using STEAM technology for preschool-aged children, the development of logical thinking skills through STEAM education, design activities, and the advantages of engineering activities for children
Keywords: Creativity, imagination, emotions, initiative, mobility, and adaptability in children; the formation of logical thinking, engineering, design, independence in the educational process, integrated learning, STEAM activities, and project-based learning in preschool education.